Comparative Economic Performance: Poland and the European Union - Zbigniew Matkowski; Ryszard Rapacki; Mariusz Prochniak (Poland. Competitiveness Report 2016. The Role of Economic Policy and Institutions, 2016)
The aim of this chapter is to assess changes in the competitiveness of the Polish economy from 2010 to 2015. The analysis covers the basic indicators of economic development, such as GDP growth, inflation, unemployment, balance of public finances, and current account balance. Poland's economic indicators are compared with those reported by other European Union member states.
Keywords: E60; E63; O40; O52; O57; 330; macroeconomic performance; economic growth; European Union